Hemoglobin Oxidation in Stored Blood Accelerates Hemolysis and Oxidative Injury to Red Blood Cells - Mustafa, Ibrahim; Hadwan, Tameem Ali Qaid (Journal of Laboratory Physicians, 2020)
Introduction Maintaining blood supply is a challenge in blood banks. Red blood cells (RBCs) stored at 4°C experience issues of biochemical changes due to metabolism of cells, leading to changes collectively referred to as “storage lesions.” Oxidation of the red cell membrane, leading to lysis, contributes to these storage lesions.Methods Blood bags with CPD-SAGM stored at 4°C for 28 days were withdrawn aseptically on days 1, 14, and 28. Hematology analyzer was used to investigate RBC indices. Hemoglobin oxidation was studied through spectrophotometric scan of spectral change. RBC lysis was studied with the help of Drabkin's assay, and morphological changes were observed by light and scan electron microscopy.Results RBCs show progressive changes in morphology echinocytes and spherocytes on day 28. There was 0.85% RBC lysis, an approximately 20% decrease in percentage oxyhemoglobin, and a 14% increase in methemoglobin formation, which shows hemoglobin oxidation on day 28.Conclusions Oxidative damage to RBC, with an increase in storage time was observed in the present study. The observed morphological changes to RBC during the course of increased time shows that there is progressive damage to RBC membrane and a decrease in hemoglobin concentration; percentage RBC lysis is probably due to free hemoglobin and iron.
Keywords: storage lesions; erythrocytes; free hemoglobin; iron